Case report: A novel occurrence of persistent left cranial vena cava coexisting with polycystic kidney disease in a cat - Cha, Ye-Eun; Ro, Woong-Bin; Song, Seung-Ji; Lee, Mi-Kyung; Kang, Min-Hee; Park, Hee-Myung (Frontiers in Veterinary Science, 2023)
A 7-year-old castrated male Munchkin cat was presented with anorexia. This cat had been diagnosed with chronic kidney disease due to polycystic kidney disease. Tachycardia with a systolic murmur (grade III/VI) was auscultated and for further diagnosis, echocardiography was performed. Based on echocardiography, persistent left cranial vena cava (PLCVC) was suspected due to enlargement of the coronary sinus and confirmed by saline contrast echocardiography. The dilated coronary sinus compressed the left atrium, and left ventricular hypertrophy with the systolic anterior motion of the mitral valve, aortic regurgitation, and mitral regurgitation were identified. After medical management using atenolol, left atrial function and other hemodynamics of the heart were improved, including the disappearance of regurgitation and normalization of left ventricular wall thickness. This case report describes the echocardiographic characteristics, diagnostic procedures, and disease progression in a cat with PLCVC after medical management using atenolol. Additionally, this is the first report of a cat with PLCVC, coexisting with polycystic kidney disease.